Prevent Stunting by Cultivating Native Chickens in Banyusidi Village - Rasminati, Nur; S.Pt.,M.Pt., IPP., ir. Ajat Sudrajat; Utomo, Setyo; Purwani, Tyastuti; Pusparatri, Allycia Ayu; Ismail, Fazhana (Farmers: Journal of Community Services, 2025)
Dayugo Hamlet is one of the hamlets in Banyusidi village which is included in the area of District, Magelang Regency. The number of couples of childbearing age is 70 people with the number of children under five years old (Toddlers) is 23 people. of that number, 5 children under five will experience stunting in 2024. The purpose of this activity is to overcome stunting by improving parenting and increasing understanding of the importance of nutrition for through the consumption of chicken eggs. Therefore, the solution offered is awareness for couples of childbearing age about the importance of nutrition for the growth and development of children in the womb until the age of 5 years.  Empowerment of through consumption patterns and deversification of daily menus. Before the activity, a survey will be conducted about the level of awareness of about parenting and the importance of nutrition. The output targets to be achieved are the emergence of awareness to change consumption patterns and parenting patterns (80%), no more stunting toddlers (0%), there is menu deversification  and toddlers made from free-range chicken eggs.  The activity began with awareness through AMT (Achievment Motivation Training) for pregnant women and mothers with toddlers with indications of stunting. Then training on optimizing the maintenance of free-range chickens, egg processing training and toddlers. The results of the evaluation of the activities carried out through the questionnaire showed that 90% of the participants understood and realized the need for regular consumption of eggs and vegetables and toddlers, and 80% of participants actively participated in the use of yards for vegetable plants and 100% were present in making processed eggs and vegetables and toddlers. The number of stunted toddlers in Dayugo hamlet, which at the beginning of the activity amounted to 5 children, was successfully reduced to 0 children, meaning that the activities carried out were able to provide benefits and could reduce the number of stunted toddlers.